Measuring human wellbeing: A protocol for selecting local indicators. Issue 114 (December 2020) - Loveridge, Robin; Sallu, Susannah M; Pesha, Ignatus J; R Marshall, Andrew
Highlights: Clear methods are needed to measure human wellbeing in support of environmental policy Wellbeing assessments need to balance trade-offs between complexity and simplicity in order to be practical to implement We present and test a wellbeing indicator selection protocol for measuring human wellbeing 111 candidate indicators were simplified to a 19-indicator index that explained 91% of variation in the 111 indicators The protocol combines top-down and bottom-up perspectives to ensure statistical rigor and local relevance Abstract: Improving human wellbeing is a major focus of international environmental and sustainable development policy. However, clearly defined measures of wellbeing are needed as an empirical base for the formulation and evaluation of policies. Despite conceptual progress towards agreement of universally relevant dimensions of wellbeing, consensus is still lacking on how to translate these dimensions into locally appropriate indicators to measure wellbeing in different contexts. This paper focuses on three interrelated challenges associated with this knowledge gap: (1) navigating trade-offs between complexity versus simplicity of concept; (2) integrating top-down and bottom-up perspectives; (3) ensuring a cost-effective and flexible approach suitable for different policy contexts. We contribute to filling this gap by developing a step-by-step Wellbeing Indicator Selection Protocol (WISP) for measuring wellbeing. The protocol integrates perspectives through an interdisciplinary mixed methods design that includes cross-validation between quantitative approaches of redundancy analysis and statistical modelling and qualitative approaches of focus groups and thematic analysis. In this way we promote a pragmatic approach suitable for a range of social and environmental contexts. We tested WISP in rural Tanzania, identifying 111 candidate wellbeing indicators. This list was simplified to a subset of 19 indicators that retained 91 % of measured variation among all wellbeing indicators. The simplified list was representative of both a multidimensional concept of wellbeing and the diversity of opinions sampled. We conclude that the protocol provides practical, statistically validated guidance to support the design of wellbeing assessments, maintaining coherence between universal theory and local realities.